Dental care for children with autism spectrum disorder - Amrita Widyagarini; Margaretha Suharsini (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Providing dental treatment for children with autism spectrum disorder (ASD) represents a challenge for dentists. In the dental care of such children, the treatment plans implemented are usually determined by several factors, including: the type of autism spectrum disorder, the degree of patient cooperation, dentist/patient communication, the required treatment, self-care skills and parental/dentist support. Purpose: The purpose of this case report was to report the dental care delivered in the cases of two pediatric patients with ASD. Case 1: A 10.7 year-old boy with a nonverbal form of ASD who was experiencing recurrent pain in his lower left posterior tooth and also presented a blackened tooth. Case 2: A 9.6 year-old boy with a nonverbal form of ASD suffering from numerous painful cavities. Case management 1: On the day of the first visit, the boy was the subject of several behavioral observations. During the day of the second visit, he underwent a brief intraoral examination at a dental unit in order to arrive at a temporary diagnosis before appropriate was decided upon treatment in consultation with his parents. The implemented treatment plans comprised dental extraction and preventive restoration under general anesthesia. Case management 2: On the first visit, the boy underwent behavioral observations followed by early intraoral examination involving physical restraint approach. During the second visit, several treatment plans such as: general anesthesia, tooth extraction, restoration, and pulp-capping treatment were formulated. Conclusion: It can be concluded that general anesthesia was considered an appropriate dental treatment plan since the two patients in question were extremely co-operative during the necessary procedures. In other words, pediatric dental care treatment plans in cases of ASD should be determined by clearly-defined criteria, specifically the benefits and risks of the treatment plans for the safety of both patient and dental care team.